2018
DOI: 10.5812/ijpbs.8074
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of Brain Functions: A Randomized Single-Blinded Observational Study

Abstract: Background: Cerebral dominance, also known as lateralization of brain functions, is the neurologic phenomenon in which one hemisphere dominates over the other. In humans, the majority of people are of left cerebral dominance. This study aims to derive a statistical inference between determined parameters of cerebral dominance (handedness, gender, and language skills) and the 3-dimensional visual analytic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Further, trends databases, including Google Trends, can be explored in connection with the topic of pre-mortem psychedelic tripping to assess the digital epidemiology and geography of people interested in the subject. It is also essential to inspect the concepts of cerebral dominance (lateralisation of brain functions), manifested as patterns of handedness in the population, that may interfere with the decision-making process (Al-Hadithi, Al-Imam, Irfan, Khalaf, & Al-Khafaji, 2016;Al-Hadithi & Al-Imam, 2017;Al-Imam, 2017e;Al-Imam, 2018;Al-Imam, Ali, & Saad, 2018). Additionally, online and offline surveys and interviews should be deployed to reduce the reliance on web snapshot technique that is prone to errors and biases.…”
Section: Discussionmentioning
confidence: 99%
“…Further, trends databases, including Google Trends, can be explored in connection with the topic of pre-mortem psychedelic tripping to assess the digital epidemiology and geography of people interested in the subject. It is also essential to inspect the concepts of cerebral dominance (lateralisation of brain functions), manifested as patterns of handedness in the population, that may interfere with the decision-making process (Al-Hadithi, Al-Imam, Irfan, Khalaf, & Al-Khafaji, 2016;Al-Hadithi & Al-Imam, 2017;Al-Imam, 2017e;Al-Imam, 2018;Al-Imam, Ali, & Saad, 2018). Additionally, online and offline surveys and interviews should be deployed to reduce the reliance on web snapshot technique that is prone to errors and biases.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between handedness and complex visual analytic skills has been studied before, emphasising on the significance of handedness, cerebral dominance patterns, and visual skills (11)(12)(13)(14)(15). Gauthier, Kanwisher, McCarthy, Casper, and colleagues investigated specific areas of the brain in relation to face recognition abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Al-Imam et al suggested further studies on a specific population, including users of novel psychoactive substances (NPS). The analyses can be further extended to include visual analytic skills and face recognition abilities (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers should attempt to study osteology as well as radiology-based samples and compare the results from each to contrast premortem and postmortem specimens. They should also study and compare different ethnicities, age groups, patterns of lateralization of brain functions for the potential modifier effect on the stomatognathic system [51,52]. Research can involve individuals with pathologies and conditions of interest, for example, those with alveolar osteitis, pterygoid implants, dental prostheses, and ailments that can affect bone density and microstructure.…”
Section: K-means and Hierarchical Cluster Analysismentioning
confidence: 99%